The Effect of The Let’s Read Website toward Students’ Reading Ability of Class VIII at Madrasah Tsanawiyah Pancasila Bengkulu - Malika Diah Puspita Sari; M. Arif Rahman Hakim; Pebri Prandika Putra (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
Reading is a fundamental language skill that involves not only recognizing words but also understanding the meaning of a text. This study aims to examine the impact of using the Let's Read website on the reading ability of eighth-grade students at Madrasah Tsanawiyah Pancasila, Bengkulu City. A quantitative approach with a quasi-experimental design was employed. Participants were divided into two groups: an experimental group that used the Let’s Read website as a learning medium, and a control group that received instruction through conventional methods. Data were collected using a multiple-choice test consisting of 25 questions, administered before and after the intervention. To analyze the data, the Mann–Whitney U test was used to compare learning outcomes between the two groups, while the Wilcoxon Signed Rank test was applied to evaluate improvements within each group. The results of the Mann–Whitney U test showed a significance value of 0.379 (p > 0.05), indicating no statistically significant difference between the experimental and control groups. However, the Wilcoxon test showed significant results for both groups, suggesting that students in both the experimental and control groups experienced a significant improvement in their reading skills after the learning process. Therefore, it can be concluded that although the Let’s Read website contributes to improving students’ reading skills, it does not produce a significantly greater effect than conventional teaching methods